An Overview of Enabling Green Cellular Networks (International Journal of Innovative Research in Computer Science & Technology, 2020)
For the last few 70 years, phone systems  have completely changed how users control network  connections, but they actually needed a meaningful effort  and time from drivers to advance a technology modems  that was developed with low deployment costs, widespread  coverage, and customer satisfaction attacks in mind.  Because of their large energy consumption, traditional  "macro" Base Stations (BSs) have proved to be  insignificant in terms of running costs in the past. Green  communication is becoming one of the key design goals  for future mobile networks, and current research is targeted  at allowing long-term development of wireless data  equipment. Several approaches to enhancing the efficiency  of wireless devices have really been proposed so far. Small  cells with low-cost, minimal Access Points (APs)hold  promise for limiting emission power and improving  spectral efficiency. By adjusting network settings to load  changes while meeting quality requirements, dynamic  radio resource management may minimize energy waste.  APs can adjust their operating points to changing  circumstances thanks to flexible hardware platforms. This  survey makes a three-fold contribution. We examine the  literature-based methods for evaluating modern wireless  platform's energy usage There are examples of green  performance measure and have been used and potential  export that have also been considered. Finally, basing on a  hypothesized category, we describe and critically assess  energy conservation accelerators recently offered by the  telecom community.
Keywords: Cellular Networks; Energy Consumption; Energy Efficiency (EE); Green Metrics; LTE.